Clozapine-induced hypersensitivity myocarditis presenting as sudden cardiac death - Natraj Katta; Sudarshan Balla; Kul Aggarwal (University of São Paulo, 2016)
Hypersensitivity myocarditis is a rare but serious adverse effect of clozapine, a commonly used psychiatric drug. We report the case of sudden cardiac death from clozapine-induced hypersensitivity myocarditis diagnosed at autopsy. A 54-year-old Caucasian male on clozapine therapy for bipolar disorder presented with a sudden onset of shortness of breath. Laboratory studies were significant for elevated N-terminal prohormone of brain natriuretic peptide. During his hospital stay, the patient died of sudden cardiac arrest from ventricular tachycardia. The autopsy revealed hypersensitivity myocarditis, which usually occurs in the first 4 weeks after the initiation of clozapine. A 4-week monitoring protocol, including laboratory assessment of troponin and C-reactive protein, may assist in the early diagnosis of this potentially fatal condition